2010
DOI: 10.1007/s00125-010-1673-4
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in glucose levels: a consequence of physiology or methodological convenience? The Inter99 study

Abstract: Aims/hypothesis We aimed to examine whether sex differences in fasting plasma glucose (FPG), 2 h post-OGTT plasma glucose (2hPG) and HbA 1c could be explained by differences in body size and/or body composition between men and women in a general non-diabetic Danish population. Moreover, we aimed to study to what degree the newly suggested high-risk HbA 1c criteria overlapped with the current OGTT-based criteria of glucose intolerance. Methods We used cross-sectional data from 6,006 nondiabetic men and women. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

19
98
2
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 114 publications
(120 citation statements)
references
References 28 publications
19
98
2
1
Order By: Relevance
“…Models for 2hPG were also adjusted for height, as previously suggested [9]. To handle the within-person correlation arising from the longitudinal structure of the dataset, random effects were included for the intercept in each model.…”
Section: Methodsmentioning
confidence: 99%
“…Models for 2hPG were also adjusted for height, as previously suggested [9]. To handle the within-person correlation arising from the longitudinal structure of the dataset, random effects were included for the intercept in each model.…”
Section: Methodsmentioning
confidence: 99%
“…Further analysis using anthropometric measures (e.g., weights, heights and waist-hip circumferences) indicated that the differences in plasma glucose levels 2 hours after oral glucose tolerance tests, but not fasting plasma glucose levels, could be explained by differences in body size and/or body composition between men and women (113,115,118,121). Consequently, women are more commonly diagnosed with diabetes on the basis of glucose level 2-hour post glucose tolerance test compared with fasting plasma glucose levels (112,115).The risk of gestational diabetes is also higher in shorter compared with taller women (122).…”
Section: Sex Difference In Glucose Tolerancementioning
confidence: 97%
“…Several epidemiological investigations from European countries (111)(112)(113), Australia (114)(115)(116), Asian countries (117), and Mauritius (118) report that men have higher fasting plasma glucose levels and plasma glucose levels during the early course of the oral glucose tests than women, indicating that the prevalence of impaired fasting glycaemia is higher in men than in women; and women have higher plasma glucose levels 2 hours after oral glucose tolerance tests than men, suggesting that the prevalence of impaired glucose tolerance is higher in women than in men. The pre-diabetic condition of impaired fasting glycaemia is characterized by hepatic insulin resistance, elevated hepatic glucose production and beta cell dysfunction.…”
Section: Sex Difference In Glucose Metabolismmentioning
confidence: 99%
See 2 more Smart Citations